OCT-A monitoring of the efficacy of neuroprotective therapy for glaucomatous optic neuropathy - N.G. Glazko; A.E. Egorov (РМЖ "Клиническая офтальмология")
N.G. Glazko1,2, A.E. Egorov1,2 1Hospital for Disabled Veterans No. 2, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation Abstract Aim: to describe morphological functional changes in patients with primary open-angle glaucoma (POAG) with good vision and controlled intraocular pressure (IOP) after trophic modified laser coagulation. Patients and Methods: 45 patients (78 eyes) aged 45–80 years with moderate and advanced POAG lasting at least one year were enrolled in the study. All patients underwent general examination (complaints and history taking) and ocular examination (visual acuity, IOP, slit lamp exam, eye fundus exam, and optical coherence tomography angiography (OCT-A) to assess foveal avascular zone (FAZ)). In addition, all patients were invited to complete a questionnaire to measure subjective perception of their vision. The examinations were performed before the treatment, the next day after trophic modified laser coagulation, the next day after administering bovine retinal polypeptides, and 7 days after starting treatment. Trophic modified laser coagulation included two steps, i.e., creation of areas of increased blood-ocular barrier permeability and administration of bovine retinal polypeptides into these areas. Results: in patients with controlled POAG and good vision, positive changes in FAZ parameters (as demonstrated by OCT-A) as well as subjective improvement of vision (as demonstrated by completing questionnaire before and after the treatment) were revealed after trophic modified laser coagulation. Conclusions: our findings demonstrate the efficacy of neuroretinoprotection for glaucomatous optic neuropathy due to the improved microcirculation and activation of foveal blood flow. Keywords: optical coherence tomography angiography, primary open-angle glaucoma, glaucomatous optic neuropathy, neuroretinoprotection, trophic modified laser coagulation, bovine retinal polypeptides. For citation: Glazko N.G., Egorov A.E. OCT-A monitoring of the efficacy of neuroprotective therapy for glaucomatous optic neuropathy. Russian Journal of Clinical Ophthalmology. 2020;20(1):–7. DOI: 10.32364/2311-7729-2020-20-1-2-7.